The emerging data on choice of optimal therapy for locally advanced nasopharyngeal carcinoma. Issue 3 (May 2020) - Hui, Edwin Pun; Ma, Brigette B.Y.; Chan, Anthony T.C.
Abstract : Purpose of review: We focus on the emerging data from randomized clinical trials for optimal integration of induction, concurrent, and/or adjuvant chemotherapy with intensity-modulated radiotherapy in locally advanced nasopharyngeal carcinoma (NPC), and the use of plasma Epstein–Barr virus (EBV) DNA for risk stratification. Recent findings: Several phase 3 trials have shown that induction chemotherapy followed by concurrent chemoradiation (CRT) improved overall survival or disease-free survival when compared to CRT alone in stage III/IV NPC who is at high risk of distant metastases. The benefit of adjuvant chemotherapy following CRT when compared to CRT alone is uncertain. There are increasing clinical data supporting the use of plasma EBV DNA for risk stratification. There are growing clinical data supporting the integration of immune checkpoint inhibitors into the induction, concurrent, and/or adjuvant/maintenance phase of treatment in locally advanced NPC. Summary: Concurrent chemoradiation remains the standard treatment backbone in locally advanced NPC. There is level 1 evidence for induction chemotherapy followed by CRT in stage III/IV NPC. There is increasing evidence against the indiscriminate use of adjuvant chemotherapy following CRT. With the increasing treatment intensification, future treatment algorithm in NPC should incorporate plasma EBV DNA and other biomarkers for risk stratification and treatment selection.